Distinct neuronal excitability alterations of medial prefrontal cortex in early‐life neglect model of rats. Issue 3 (23rd June 2022) - Zhang, Yu; Sun, Xiuping; Dou, Changsong; Li, Xianglei; Zhang, Ling; Qin, Chuan
Abstract: Object: Early‐life neglect has irreversible emotional effects on the central nervous system. In this work, we aimed to elucidate distinct functional neural changes in medial prefrontal cortex (mPFC) of model rats. Methods: Maternal separation with early weaning was used as a rat model of early‐life neglect. The excitation of glutamatergic and GABAergic neurons in rat mPFC was recorded and analyzed by whole‐cell patch clamp. Results: Glutamatergic and GABAergic neurons of mPFC were distinguished by typical electrophysiological properties. The excitation of mPFC glutamatergic neurons was significantly increased in male groups, while the excitation of mPFC GABAergic neurons was significant in both female and male groups, but mainly in terms of rest membrane potential and amplitude, respectively. Conclusions: Glutamatergic and GABAergic neurons in medial prefrontal cortex showed different excitability changes in a rat model of early‐life neglect, which can contribute to distinct mechanisms for emotional and cognitive manifestations. Abstract : Early‐life neglect have irreversible emotional effects to central nervous system. Herein this work, we were aimed to decipher distinct functional neural changes in medial prefrontal cortex of model rats. Maternal separation with early weaning were taken as rat model of early‐life neglect. The excitation of glutamatergic and GABAergic neurons in rat mPFC were recorded and analyzed by whole‐cell patch‐clamp. Glutamatergic and GABAergic neurons of mPFC were distinguished by typical electrophysiological properties. The excitation of mPFC Glutamatergic neurons were significant increase in male groups, while the excitation of mPFC GABAergic neurons were more significant in female groups. Glutamatergic and GABAergic neurons in medial prefrontal cortex showed different excitability changes in rat model of early‐life neglect, which can contribute to distinct mechanisms for emotional and cognitive manifestations.